An experiment study on submersible unmanned aerial vehicle - Tan, Wee Kiat (2018)
An unmanned aerial vehicle (UAV) that can function as an autonomous underwater vehicle (AUV) below the water surface has increased operations capability. This mode of operations has significant benefits as an economic and flexible search-and-rescue or surveillance platform. There are challenges in developing the submersible UAV, and one of the major challenges is the transition from air to water. For this project, the plunge-diving method is proposed as it has passive hydrodynamic stability when diving into the water and the vehicle does not need to know its height from the water surface. However, there is limited information on designing a UAV capable of withstanding direct water impact and integration of subsystems that can work in both air and water. The project’s objectives are to conduct an experimental study on submersible UAV to evaluate its technical feasibility by conducting water impact investigation, and design and develop a conceptual submersible UAV. The water impact investigation is focusing on experimental testing to determine the relationship between impact force, nosecone shape and mass. At the current stage, power series nosecone was used as it has the least increase in impact force with increase in mass. The design and development of the submersible UAV have reached the assembly and subsystem testing stages. The subsystem tests show that the UAV mechanism performs less than expected and will require improvement. Also one of the critical problems is the UAV overall weight is higher than estimated. Overall this project manages to meet all the objectives and it shows that it was technically feasible to design and develop a submersible UAV with current technology.